Avaliando o desempenho da indústria brasileira - Márcio Jorge Mendonça; Rodrigo Mendes Pereira; Beatriz Pinna; Luis Alberto Toscano Medrano (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
In this study we investigate the performance of Brazilian industry based on productivity and efficiency indicators. We associate productivity with the concept of total factor productivity (TFP) while efficiency is measured based on the stochastic frontier production model that indicates how far the actual production deviates from the optimal level. This methodology allows to take into consideration the effect of non-manageable factors o. Both models make use of Annual Industrial Survey (AIP) data for 29 Brazilian industrial sectors for the period 2007 to 2019. The results derived from TFP show that between 2010 and 2016, Brazilian industry experienced a productivity loss of 15.7%. Our frontier model allows to identify the evolution of efficiency over time. The results indicate there was also a downward trend in efficiency in the Brazilian industry. Among the exceptions is the Oil and Natural Gas Extraction sector that jumped from 29th place in 2007 to second place in 2019. This rise, which begins to happen in 2010, is possibly due to exploration and production (pre-salt) and in the refining area, resulting in the large increase in investment in the sector.
Keywords: L6; O1; 330; total factor productivity; Annual Industrial Survey; solow residual; capital; perpetual inventory method